Pemanfaatan Bahan Makanan Tradisional Tempe Kedelai Sebagai Menu Andalan Hotel - Pirastyo, Swastono Putro; Kristiutami, Yuliana Pinaringsih (Universitas Pendidikan Indonesia, 2018)
Tempe is one famous traditional food from Indonesia. Tempe can be process into so many variety of food with delicious taste. But in hospitality industries, the utilization of tempe is not maximal yet. This research is to find out the utilization of tempe in Jadul Village Resort and Spa. This research is also wanted to find how often tempe used in the menu, and how good the demand of the tempe itself. After this research, hopefully tempe can used more often as the main course menu, or as side dishes. And hopefully,Â tempe can dreated into signature dishes that represent Jadul Village Resort and Spa as a resort with the Indonesian specialty.